Aerodynamic Characteristics Evaluation of a Cable-Stayed Bridge Section with a New-Type Hybrid Fairing - Hoyeop Lee; Jiho Moon (Shock and Vibration)
In this study, new-type hybrid faring is suggested to improve the aerodynamic performance of the long-span cable-stayed bridge. The proposed fairing is developed by applying the concept of the multibox section to the normal faring. The proposed faring has void regions inside the faring so that wind passes through the gaps in the faring. As a result, the wind flow is changed and the forces to the bridge section are reduced. The efficiency of the proposed faring was verified by a series of wind tunnel test. From the test result, it can be found that aerodynamic performances, such as drag force and flutter resistance, are enhanced.